β-Hydroxybutyrate-induced mitochondrial DNA (mtDNA) release mediated innate inflammatory response in bovine mammary epithelial cells by inhibiting autophagy - Yihui Huo; Taiyu Shen; Tianyin Feng; Moli Li; Wanli Zhao; Juan J. Loor; Ben Aernouts; Androniki Psifidi; Chuang Xu (Journal of Animal Science and Biotechnology)
Abstract Background In perinatal dairy cows, ketosis is a prevalent metabolic disorder that lowers milk output and performance. Mitochondrial dysfunction and chronic inflammation in mammary tissue are linked to elevated blood ketone levels, particularly β-hydroxybutyrate (BHB). Recent research has linked cytosolic mitochondrial DNA (mtDNA) with chronic aseptic inflammation by activating the cGAS-STING pathway during metabolic disorders, while autophagy activation effectively reverses this process. However, whether it is involved in mammary gland damage during ketosis is poorly understood. Therefore, this study aimed to explore the underlying mechanisms of mtDNA-induced inflammation under BHB stress and evaluate the potential therapeutic strategy of autophagy activation in mitigating this damage. Results Our study found an increased cytoplasmic mtDNA abundance in mammary gland tissues of dairy cows with ketosis and bovine mammary epithelial cell line (MAC-T) subjected to BHB stress. Further investigations revealed the activation of the cGAS-STING pathway and inflammatory response, indicated by elevated levels of cGAS and STING, along with increased phosphorylation levels of TBK1, P65, and IκB, and higher transcript levels of pro-inflammatory factors (IL-1B, IL-6, and TNF-α) in both in vivo and in vitro experiments. Notably, STING inhibition via si-STING transfection reversed BHB-induced inflammation. Additionally, autophagy activation appeared to protect against BHB stress by facilitating the removal of cytoplasmic mtDNA and preventing cGAS-STING pathway-mediated inflammation. Conclusions The findings illustrate that elevated BHB levels lead to the release of cytoplasmic mtDNA, which in turn activates the cGAS-STING pathway and triggers an inflammatory response in the mammary glands during hyperketonemia. Conversely, autophagy activation has been shown to alleviate this process by promoting cytoplasmic mtDNA degradation. Graphical Abstract